STRATEGI PENGEMBANGAN KEPARIWISATAAN DI KOTA BUKITTINGGI - Sanesta, Aldian; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Development Strategy of turism at Bukittinggi City. Bukittinggi City Tourism Development is an area of the city and one of the main tourist destination in West Sumatra with the introduction of Bukittinggi as a